2016
DOI: 10.1080/00918369.2016.1190218
|View full text |Cite
|
Sign up to set email alerts
|

Is the Lack of Specific Lesbian, Gay, Bisexual, Transgender and Queer/Questioning (LGBTQ) Health Care Education in Medical School a Cause for Concern? Evidence From a Survey of Knowledge and Practice Among UK Medical Students

Abstract: Lesbian, gay, bisexual, transgender and queer/questioning (LGBTQ) people frequently report negative health care encounters. Medical professionals may inadequately manage LGBTQ persons' health if they have not received training in this area. An anonymous survey measuring efficacy in health situations among LGBTQ persons was answered by 166 medical students across all years of a UK university. Results show that 84.9% of participants reported a lack of LGBTQ health care education, with deficits in confidence clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
118
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 22 publications
4
118
1
6
Order By: Relevance
“…10,14,15 With regard to education, especially in the context of principles of adult learning, existing studies call for developing competencies that encompass critical knowledge, skills and attitudes needed to provide affirmative care to LGBT people. [4][5][6][7][8]11 These cannot be measured in hours, but through comfort with effective communication and patient satisfaction. A curricular resource with suggested milestones has been developed by the Association of American Medical Colleges that can serve as a guide for educational programs seeking to expand LGBT health training.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,15 With regard to education, especially in the context of principles of adult learning, existing studies call for developing competencies that encompass critical knowledge, skills and attitudes needed to provide affirmative care to LGBT people. [4][5][6][7][8]11 These cannot be measured in hours, but through comfort with effective communication and patient satisfaction. A curricular resource with suggested milestones has been developed by the Association of American Medical Colleges that can serve as a guide for educational programs seeking to expand LGBT health training.…”
mentioning
confidence: 99%
“…4,5 As recently as a decade ago there were no standard texts that included information about care for LGBT people, and numerous studies and reviews of health issues have documented a continued gap in health care education. [4][5][6][7] A study of LGBT topics in medical education published in 2011 showed a median of 5 h of education in both the US and Canada. 8 It is not surprising that despite demonstration of health disparities experienced by LGBT people across the life cycle, many LGBT people find it difficult to access quality care.…”
mentioning
confidence: 99%
“…It has become clear, through this review, that issues exist around the development of cultural competence to enable practitioners to deliver care and supports in culturally responsive, sensitive and inclusive ways (Corliss et al, 2007;Fredriksen-Goldsen et al, 2011;Carabez et al, 2015b;Chen and Yang, 2015;Walsh and Hendrickson, 2015;Echezona-Johnson, 2017;Parameshwaran et al, 2017). In one UK study involving medical students, where almost 85% of participants reported a distinct lack of LGBT+ education, nearly half said that they would not routinely ask about sexuality or gender identity needs when assessing patients.…”
Section: Developing Cultural Competence and Inclusivitymentioning
confidence: 99%
“…A score of zero was given if the paper contained no information, one if there was a moderate amount, and a score of two if the question was fully addressed (Rushbrooke et al, 2014). A total of 13 studies scored 17 and above (Bidell, 2017;Carabez et al, 2015b;Daley and MacDonnell, 2015;Echezona-Johnson, 2017;Grosz et al, 2017;Kelley et al, 2008;Lim et al, 2015;Obedin-Maliver et al, 2011;Parameshwaran et al, 2017;Rogers et al, 2013;Strong and Folse, 2014;Walsh and Hendrickson, 2015;White et al, 2015). A total of 9 studies scored between 14 and 16, indicating gaps and limitations in relation to aims, data collection methods, and ethical concerns (Carabez et al, 2015a;Cheng & Yang 2015;Corliss et al, 2007;Fredriksen-Goldsen et al, 2011;Gendron et al, 2013;Hardacker et al, 2014;Röndahl, 2011;Sequeira et al, 2012;Vance et al, 2017).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation